Qualitative methodogy: revealing a new path for research in dentistry - Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Arcieri, Renato Moreira [UNESP]; Lima, Thaís Jaqueline Vieira de [UNESP] (My University, 2013)
Currently, it is easy to find health professionals who not only attach importance to qualitative methods, but also recognize their help to better understand their patients' lives. However, its use in dentistry is still incipient, either due to ignorance or because of technical / operational difficulties in identifying possibilities for their use in research. Thus, the purpose of this study was to review the literature on the characteristics and peculiarities of the qualitative methodology, demonstrating their techniques of collecting, recording and analyzing data. For this, we performed a descriptive literature, from a survey in the "LILACS", "BBO" and "PUBMED" databases, by keywords related to the theme, selecting only the papers that mentioned the "importance" of qualitative research, the "characteristics and fundamentals," and the "techniques of collecting, recording and data analysis" involving this methodology. It was found that all studies have highlighted the importance of qualitative research to the construction of new knowledge that cannot be achieved by quantitative data. We found many different techniques to gather, record and analyze qualitative data applied to the dentistry field. It was concluded that qualitative research represents a new path to be followed by dentistry, so that we are able to plan actions in ethical and humane public health dentistry, bringing better results to the population, because of the depth of knowledge that your date can.

Atualmente, é fácil encontrar profissionais de saúde que não somente atribuem importância aos métodos qualitativos, mas também reconhecem sua ajuda para melhor compreender a vida dos pacientes. No entanto, na Odontologia seu uso ainda é incipiente, seja por desconhecimento ou por dificuldades técnicas/operacionais em identificar possibilidades para seu uso em pesquisa. Assim, o objetivo deste trabalho foi realizar uma revisão da literatura sobre as características e peculiaridades da metodologia qualitativa, evidenciando suas técnicas de coleta, registro e análise de dados. Para isso, foi realizada uma pesquisa bibliográfica descritiva, partindo de um levantamento nas bases de dados “LILACS”, “BBO” e “PUBMED”, através de palavras-chaves relacionadas ao tema, selecionando apenas os trabalhos que mencionassem a “importância” da pesquisa qualitativa, suas “características e fundamentos”, e as “técnicas de coleta, registro e análise de dados” que envolvem esta metodologia. Verificou-se que todos os trabalhos ressaltaram a importância da pesquisa qualitativa para a construção de novos conhecimentos que não podem ser alcançados pelos dados quantitativos. Foram encontradas várias técnicas para coletar, registrar e analisar dados qualitativos, sendo sua aplicação exemplificada na área da Odontologia. Concluiu-se que a pesquisa qualitativa representa um novo caminho a ser trilhado pela Odontologia, para que se tenha condições de planejar ações éticas e humanizadas em saúde bucal coletiva, trazendo melhores resultados à população, em razão da profundidade de conhecimento que seus dados podem gerar.
Metodologia qualitativa: evidenciando um novo caminho para a pesquisa em odontologia
Keywords: Investigative techniques; Qualitative analysis; Qualitative research; Técnicas de pesquisa; Análise qualitativa; Pesquisa qualitativa